THE RELATIONSHIP OF NITRATE AND PHOSPHATE WITH ABUNDANCE OF EPIPELIC IN THE WATERS OF SUNGAITOHOR VILLAGE, REGENCY OF MERANTI ISLANDS, RIAU PROVINCE - Beranda, Ongki Okto; Amin, Bintal; Siregar, Sofyan Husein (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
The study was conducted in August-October 2019. Aims to determine theconcentration of nitrate, phosphate, uniformity index, diversity and index of dominancy,abundance of epipelic diatoms and know the relationship between nitrate,phosphate and epipelic abundance diatoms in the water area of Sungaitohor Desa Meranti of Riau Islands district. The method used in this research is a surveymethod consisting of 4 research stations. Location of observation and sampling is in the waters of Muara Sungaitohor Kabupaten Meranti Islands. Basedon the results of this study of nitrateconcentrations in the waters of Sungaitohor Bekisar village 0,068-0,092 mg/l, phosphate concentrations ranged0,097-0,220 mg/L. The Epipelic diatom found in the water area of Sungaitohorvillage amounted to 14 types. As for the abundance of type diatomsepipelics ranged from 27,531.72– 40,531.72 ind/cm2. From theCalculation of the community structure diatoms epipelic obtained diversityindex value (H ') which indicates a low index value of h ' has a value of2.7527 and is at a range of 1 ≤ H ' ≤ 3. The uniformity index (E) indicatesthat an epipelic spread is not balanced with an average value of 0.3643uniformity and is at a range of value ≤ 0.5. Meanwhile, the Dominance index (D)shows the value of 0.1704 where the value of the area in the waters of Sungaitohor village does not dominate. The relationship of abundance ofepipelic diatoms with the concentration of nitrate is positive and very weak,with a correlation coefficient of R = 0.0030. While the relationship ofAbundance diatomic epipelic relationship with phosphate concentrations isnegative and weak, with a correlation coefficient r = 0.262. Abundance ofdiatomic epipelics is directly proportional to the concentration of nitrate andinversely proportional to phosphate concentrations.